Lower participation among immigrants in colorectal cancer screening in Norway - Bhargava, Sameer; Botteri, Edoardo; Berthelsen, Mona; Iqbal, Nadia; Randel, Kristin Ranheim; Holme, Øyvind; Berstad, Paula (Frontiers in Public Health, 2023)
Introduction Organized cancer screening programs should be equally accessible for all groups in society. We assessed differences in participation in colorectal cancer (CRC) screening among different immigrant groups. Methods Between 2012 and 2019, 140,000 individuals aged 50 to 74 years were randomly invited to sigmoidoscopy or repeated faecal immunochemical test (FIT) in a CRC screening trial. In this study, we included 46,919 individuals invited to sigmoidoscopy and 70,018 invited to the first round of FIT between 2012 and 2017. We examined difference in participation between non-immigrants and immigrants, and within different immigrant groups by geographic area of origin, using logistic regression models, adjusted for several sociodemographic factors and health factors. Results In total, we included 106,695 non-immigrants and 10,242 immigrants. The participation rate for FIT was 60% among non-immigrants, 58% among immigrants from Western countries and 37% among immigrants from non-Western countries. The participation rate for sigmoidoscopy was 53% among non-immigrants, 48% among immigrants from Western countries and 23% among immigrants from non-Western countries. Compared to non-immigrants, multivariate adjusted odds ratio for non-participation in FIT screening was 1.13 (95% confidence interval 1.04–1.23) and 1.82 (1.69–1.96) for immigrants from Western and non-Western countries. The corresponding numbers in sigmoidoscopy screening were 1.34 (1.21–1.48) and 2.83 (2.55–3.14). The lowest participation was observed in immigrants from Eastern Europe, Northern Africa and Western Asia, and South-Central Asia. Conclusion Participation in CRC screening in Norway was particularly low among non-Western immigrants, which could put them at increased risk for late stage diagnosis of CRC. Participation was lower in sigmoidoscopy screening than in FIT screening, especially among immigrants from non-Western countries.